### Question 1. Divide 6x^{3}y^{2}z^{2} by 3x^{2}yz

**Solution:**

We can write 6x

^{3}y^{2}z^{2}as 2 * 3 * x * x * x * y * y * z * zWe can write 3x

^{2}yz as 3 * x * x * y * zNow ans = (6x

^{3}y^{2}z^{2})/(3x^{2}yz)= (2 * 3 * x * x * x * y * y * z * z)/(3 * x * x * y * z)

= 2 * x * y * z

So the answer is 2xyz

### Question 2. Divide 15m^{2}n^{3} by 5m^{2}n^{2}

**Solution:**

We can write 15m

^{2}n^{3}as 5 * 3 * m * m * n * n * nWe can write 5m

^{2}n^{2}as 5 * m * m * n * nNow ans = (15m

^{2}n^{3})/(5m^{2}n^{2})= (3 * 5 * m * m * n * n * n)/(5 * m * m * n * n)

= 3 * n

So the answer is 3n

### Question 3. Divide 24a^{3}b^{3} by -8ab

**Solution:**

We can write 24a

^{3}b^{3}as 3 * 8 * a * a * a * b * b * bNow ans = (24a

^{3}b^{3})/(-8ab)= -(3 * 8 * a * a * a * b * b * b)/(8 * a * b)

= -(3 * a * a * b * b)

= -3 * a * a * b * b

We can write -3 * a * a * b * b as -3 * a

^{2}* b^{2}So the answer is -3a

^{2}b^{2}

### Question 4. Divide -21abc^{2} by 7abc

**Solution:**

We can write -21abc

^{2}as -3 * 7 * a * b * c * cWe can write 7abc as 7 * a * b * c

Now ans = (-21abc

^{2})/(7abc)= -(7 * 3 * a * b * c * c)/(7 * a * b * c)

= -(3 * c)

= -3c

So the answer is -3c

### Question 5. Divide 72xyz^{2} by -9xz

**Solution:**

We can write 72xyz

^{2}as 8 * 9 * x * y * z * zNow ans = (72xyz

^{2})/(-9xz)= -(8 * 9 * x * y * z * z)/(9 * x * z)

= -(8 * y * z)

= -8yz

So the answer is -8yz

### Question 6. Divide -72a^{4}b^{5}c^{8} by -9a^{2}b^{2}c^{3}

**Solution:**

We can write -72a

^{4}b^{5}c^{8}as -8*9*a*a*a*a*b*b*b*b*b*c*c*c*c*c*c*c*cWe can write -9a

^{2}b^{2}c^{3 }as -9*a*a*b*b*c*c*cNow ans = (-72a

^{4}b^{5}c^{8}) /(-9a^{2}b^{2}c^{3})= (8*9*a*a*a*a*b*b*b*b*b*c*c*c*c*c*c*c*c) / (9*a*a*b*b*c*c*c)

= (8*a*a*b*b*b*c*c*c*c*c)

= 8*a*a*b*b*b*c*c*c*c*c

We can write 8*a*a*b*b*b*c*c*c*c*c as 8 * a

^{2}* b^{3}* c^{5}So the answer is 8a

^{2}b^{3}c^{5}

### Question 7. Divide 16 * m^{3} * y^{2} by 4 * m^{2} * y

**Solution:**

We can write 16m

^{3}y^{2}as 4 * 4 * m * m * m * y * yWe can write 4m

^{2}y as 4 * m * m * yNow ans = (16m

^{3}y^{2})/(4m^{2}y)= (4 * 4 * m * m * m * y * y)/(4 * m * m * y)

= (4 * m * y)

= 4my

So the answer is 4my

### Question 8. Divide 32 * m^{2} * n^{3} * p^{2} by 4 * m * n * p

**Solution:**

We can write 32m

^{2}n^{3}p^{2}as 4 * 8 * m * m * n * n * n * p * pNow ans = (32m

^{2}n^{3}p^{2}) / (4mnp)= (4 * 8 * m * m * n * n * n * p * p) / (4 * m * n * p))

= (8 * m * n * n * p)

We can write 8 * m * n * n * p as 8 * m * n

^{2}* pSo the answer is 8mn

^{2}p